Program to increase tax awareness - Rosas Prado, Carmen Elvira (2016)
The present research had as objective to increase the tax consciousness of the students of the Higher Technological Institute Public Enrique López Albujar de Ferreñafe; For which a training program consisting of 6 workshops was designed and implemented. The population was made up of 214 students from the different specialties offered by the Enrique López Albújar Higher Institute of Technology in Ferreñafe. The sample size was 78 students of the sixth cycle of the nine professional careers in that educational institution. The research design was pre-experimental with a single group, which was assessed the tax awareness through a questionnaire, before and after the treatment (training program). The results obtained through descriptive statistical analysis (tables and figures) and inferential analysis (test of hypothesis testing) significantly evidences the effectiveness of the training program in increasing students' tax awareness.